Characterization of the complete chloroplast genome of the Solanum tuberosum L. cv. Atlantic (Solanaceae). Issue 1 (2nd January 2021) - Zhang, Jing-Ying; Zhang, Jia-Yue; Zhao, Yan-Fei; Li, Shuang; Chen, Shan-Shan; Wang, Ya-Ping; Mou, Bin; Ma, Hao-Ran; Han, Zhi-Jun; Lu, Yue; Han, Yu-Zhu
Abstract: Potato ( Solanum tuberosum L.), a species of the family Solanaceae, is the fourth most important food crop worldwide. Solanum tuberosum L. cv. Atlantic, a main fried special potato, has a dry matter content of 19%–23% and a starch content of 16.26% in the tuber. In order to support more molecular data for the taxony of S. tuberosum, the complete chloroplast (cp) genome sequence of S. tuberosum L. cv. Atlantic was determined using next-generation sequencing. In leaves, the chloroplast genome accounts for 5.49% of the total genome. The entire cp genome was determined to be 155, 296 bp in length. It contained large single-copy (LSC) and small single-copy (SSC) regions of 85, 737 and 18, 373 bp, respectively, which were separated by a pair of 25, 593 bp inverted repeat (IR) regions. The genome contained 132 genes, including 87 protein-coding genes, 37 tRNA genes, and eight rRNA genes. The overall GC content of the genome is 37.9%. A phylogenetic tree reconstructed by 64 chloroplast genomes reveals that S. tuberosum L. cv. Atlantic is most closely related to Solanum tuberosum L. cv. Desiree.